"Harm as Harm": Gang Membership, Perpetration Trauma, and Posttraumatic Stress Symptoms Among Youth in the Juvenile Justice System. (May 2016) - Kerig, Patricia K.; Chaplo, Shannon D.; Bennett, Diana C.; Modrowski, Crosby A.
The construct of perpetration-induced trauma (PT) proposes that inflicting harm on others may constitute a traumatic event, a phenomenon which might be relevant to youth in gangs. This study investigated PT, trauma exposure, posttraumatic stress symptoms, and gang membership in a sample of 660 youth (484 boys, 176 girls) recruited from a detention center. When compared with their non-gang-member peers, youth in gangs endorsed higher levels of exposure to violence and PT, as well as higher symptoms of dissociation and emotional numbing. Girls who endorsed gang membership were those most likely to meet full or partial criteria for a posttraumatic stress disorder diagnosis. Results of regression analyses showed that PT predicted unique variance in posttraumatic stress above and beyond other variables and results of tests for bootstrapped indirect effects were consistent with the hypothesis that PT acts as a mediator of the association between gang membership and posttraumatic stress.